2017
DOI: 10.1177/1757177416689722
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices related to tetanus toxoid vaccination in women of childbearing age: A cross-sectional study in peri-urban settlements of Karachi, Pakistan

Abstract: Low coverage of TT vaccine is largely influenced by poor knowledge, family structure and family decision-making in the local communities of Pakistan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
4
15
0
Order By: Relevance
“…This may be a function of their knowledge of the vaccine as found in this study and others [16,28]. While age and educational status were positive predictors for tetanus toxoid uptake in some studies, one study showed an inverse relationship between protective immunity for tetanus and increasing maternal age [29,30]. The differences in findings may be a function of the variation in the studied population characteristics and differences in study designs.…”
Section: Discussionsupporting
confidence: 51%
“…This may be a function of their knowledge of the vaccine as found in this study and others [16,28]. While age and educational status were positive predictors for tetanus toxoid uptake in some studies, one study showed an inverse relationship between protective immunity for tetanus and increasing maternal age [29,30]. The differences in findings may be a function of the variation in the studied population characteristics and differences in study designs.…”
Section: Discussionsupporting
confidence: 51%
“…The analysis revealed that age of the woman increased the odds of TT vaccine uptake. This was found also in two studies done in Ethiopia which concluded the signi cance of age in uptake of TT vaccine (15,16).…”
supporting
confidence: 61%
“…17 In addition to poor care-seeking for antenatal visits during pregnancy, the lower vaccination status is also influenced by inadequate vaccination-related knowledge, family structure, and decision-making in the local communities of Pakistan. 18 Similarly, the lack of awareness about the importance of TT vaccination was reported as the most common reason for low vaccination status. 14 Adequate knowledge and a better understanding of TT vaccination at the individual, community, and national levels may significantly help to improve TT coverage in Pakistan.…”
Section: Discussionmentioning
confidence: 99%